Schistosomus reflexus em neonato de cão - Relato de caso - Léga, Elzylene; Galvão, André Luiz Baptista [UNESP]; Pinto, Mildre Loraine; Raposo, Talita Mariana Morata [UNESP]; Da Costa, Paula Ferreira [UNESP]; De Vasconcellos, Amanda Leal [UNESP]; Magalhães, Geórgia Modé [UNESP]; Jark, Paulo César [UNESP] (My University, 2013)
The Schistosomus reflexus it is an fetal monstrosity characterized by a wide opening of the thoracic and/or abdominal midline with fetal evisceration, which is associated with an intense lordosis, ankylosis and contraction of the members. This monstrosity is important in veterinary obstetrics and its occurrence is more significant in cattle and horses, and sporadic in small animals. The aim of this work is in describing a case report of Schistosomus reflexus in a newborn pinscher breed.
Schistosomus reflexus in a dog neonate - Case report
Keywords: Deformity; Fetal; Monsters